The Role of Business Sustainability in Enhancing SME Competitiveness Through Working Capital and Digital Technology - Rahmah, Mirhamida; Fatmah, Dinda; Aslikhah, Nurul; Soe, Htet Paing; Rahmah, Yusriyah; Rahmah, Zakiyah Zulfa; Purnama, Chamdan (Jurnal Manajemen dan Keuangan, 2025)
This study aims to analyze the role of business sustainability as a mediating variable in the relationship between working capital and digital technology on the competitiveness of SMEs in Indonesia. The study is motivated by the growing awareness of the importance of sustainable business practices amidst dynamic market challenges and global environmental pressures. Using a quantitative approach and path cici4d analysis techniques based on Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 200 SMES actors in the halal fashion and food sectors through structured questionnaires. The findings indicate that business sustainability acts as a significant mediator, strengthening the indirect influence of working capital and digital technology on competitiveness. These results affirm that sustainability is not merely a social responsibility, but a strategic resource that enhances the competitive position of SMEs. The adoption of digital technology and efficient working capital management will yield stronger competitive advantages when directed cici4d toward sustainability goals. This research contributes to the SMES literature and offers practical insights for business actors and policymakers in designing sustainable and competitive business strategies.